Is sentence processing really automatic? - Lin, Melicia Jia Ying (2014)
There are abundant journal articles written on Stroop effect for words. This study aims to find out 1) whether similar effects can be replicated in sentences and 2) if sentence processing has occurred during Stroop task. Thirty participants took part in two Stroop paradigm experiments. In Experiment 1, sentences were split into 3 conditions – CONTROL, CONGRUENT and INCONGRUENT. Out of these 3 conditions, only the CONTROL condition did not consist of any colour word, CONGRUENT trials were coloured in the colour word that appears in the sentence and INCONGRUENT trials were coloured differently from the colour word in the sentence. Results suggest that such effect can also be observed in sentences. For Experiment 2, only congruent trials were used. Two conditions – COLOUR CONTEXT and NON-COLOUR CONTEXT – were set up for Experiment 2. In the COLOUR CONTEXT condition, the colour word in the sentence refers to the concept of colour (eg. a blue ball). In the NON-COLOUR CONTEXT condition, the colour word in the sentence does not refer to the concept of colour (eg. out of the blue). There was no conclusive evidence suggesting that sentence processing has indeed occurred as the results were not significant. However, results were very close to significance. This may be indicative that the sentence processing did occur.